The Use of Video-Based Learning and Wordwall Quiz to Improve Students’ Understanding of Argumentative Text at Senior High School - Duwi Puspita Sari; Mohammad Sofyan Adi Pranata; Mustaina (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
This study aims to enhance students’ comprehension of argumentative texts through the implementation of Video-Based Learning combined with Wordwall Quiz in class XII IPA 4 at SMA Nurul Jadid. The participants of this research consisted of 30 twelfth-grade students. The study employed a Classroom Action Research (CAR) design, which was conducted in two cycles. Each cycle followed four systematic stages: planning, implementation, observation, and reflection. This approach allowed the researcher to continuously evaluate and improve the teaching strategy based on classroom conditions and students’ responses. Data were collected using pre-test and post-test instruments to measure students’ improvement in understanding argumentative texts. The findings revealed a significant increase in students’ achievement. The average score in the pre-test was 63, which increased to 75 in the post-test of the first cycle and further improved to 89 in the post-test of the second cycle. These results indicate a consistent improvement in students’ comprehension after the implementation of the learning media. The use of video-based learning materials proved effective in attracting students’ attention and increasing their motivation to engage with the learning content. Meanwhile, the Wordwall Quiz supported students’ understanding by providing interactive exercises and immediate feedback. In conclusion, the integration of Video-Based Learning and Wordwall Quiz is effective in improving senior high school students’ understanding of argumentative texts